2006
DOI: 10.1213/01.ane.0000205745.84044.31
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Emergence Agitation With Tropisetron or Clonidine After Sevoflurane Anesthesia in Small Children Undergoing Adenoidectomy

Abstract: Postoperative agitation is a common problem after sevoflurane anesthesia in children. In the present study, we evaluated if tropisetron or clonidine could reduce the incidence of postoperative agitation after day case adenoidectomy in small children. We included 75 unpremedicated children aged 1-7 yr who were randomly assigned to receive either placebo, tropisetron (0.1 mg/kg) or clonidine (1.5 microg/kg) after anesthesia induction. Anesthesia was induced and maintained with sevoflurane. Patients also received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 15 publications
1
24
1
3
Order By: Relevance
“…In an effort to decrease these complications, many drugs or interventions have been utilized including opioid analgesics [3][4][5], benzodiazepines [6], non-steroidal anti-inflammatory drugs [7], local anaesthetic infiltration [6,7], non-volatile induction/maintenance [7][8][9], alpha-2 agonists [1,10], tropisetron [11], caudal block [12], and delay of the emergence period [13] with various rates of success reported.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to decrease these complications, many drugs or interventions have been utilized including opioid analgesics [3][4][5], benzodiazepines [6], non-steroidal anti-inflammatory drugs [7], local anaesthetic infiltration [6,7], non-volatile induction/maintenance [7][8][9], alpha-2 agonists [1,10], tropisetron [11], caudal block [12], and delay of the emergence period [13] with various rates of success reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lankinen et al had done a study comparing the effects of intravenous clonidine 1.5 mcg/kg and tropisetron 0.1 mg/kg and found that tropisetron was more effective in reducing the incidence of emergence agitation after sevoflurane anesthesia [9]. We think that it could be due to the dosage of clonidine because intravenous clonidine 2 mcg/kg was effective according to Kulka et al, Tesoro et al and Malviya et al, although it was compared with placebo [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration of clonidine, after induction of anesthesia reduces the incidence of emergence reactions following sevoflurane administration [6][7][8]. Tropisetron, the serotonin antagonist, used as an anti-emetic, also found to be useful in reducing the incidence of the emergence agitation following sevoflurane anesthesia [9]. Midazolam, which is a shortacting benzodiazepine, is commonly used as pre-medication to reduce pre-operative anxiety and for smooth induction of anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Tropisetron proved effective for reducing emergency agitation, but clonidine did not. 46 Intravenous clonidine (2 μg/kg -1 ), administered after induction of anesthesia, reduced the incidence of emergence agitation, although there was greater postoperative somnolence, while no adverse cardiorespiratory events were observed. 44 Using more selective α 2 -agonists, an agitation incidence of 4.8% was observed among patients given dexmedetomidine, at a dosage of 1 μg/kg -1 intravenously, compared with 47.6% in a placebo group, without detecting increases in emergence time or intraoperative hemodynamic repercussion.…”
Section: Anesthetic Premedication and Adjuvant Drugsmentioning
confidence: 95%